Production of Forest Products, Not Palm Sugar Wood in Akekolano Village, North Oba District, Tidore Islands City (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to find out the production process and results of palm sugar production in Akekolano Village, North Oba District, Tidore Islands City. The research was carried out from January to June 2024. The research location was Akekolano Village, North Oba District, Tidore Islands City. This location was chosen as a research location because looking at palm sugar production in this location has quite high income potential so it is important to conduct research to look at the production process and results of palm sugar production in Akekolano Village. The results of the research show that the palm sugar production process in Akekolano Village, North Oba District, Tidore Islands City is very simple and easy, starting from the process of peeling palm fruit tangaki to the marketing process, as for the production of palm sugar for the last five months, from January 2024 until May 2024, production yields were quite high, but in April there was a significant decline because in April there was a large-scale harvest of cloves in Akekolano Village, so the palm sugar production industry players preferred to harvest cloves rather than produce them. Palm sugar.
Keywords: Forest Production; Palm Sugar; Tidore Islands City